Single layer versus double layer closure of enteric perforation- a comparative study - Pipal, Dharmendra Kumar; Verma, Vijay; Kothari, Saurabh; Pipal, Vibha R.; Sharma, Latika (International Journal of Research in Medical Sciences, 2016)
Background: Small intestine perforation and gastrointestinal haemorrhage are the most common and dreadful complications of enteric fever. There are different operative procedures available for enteric perforation repair. In the present study attempts should be made to find out which operative procedure (either single layer or double layer closure) should be planned in enteric perforation by comparing these, in terms of morbidity, mortality and cost effectiveness. Methods: This study was carried out on 50 patients of either sex. They were divided in two groups Group- A (conventional double layer repair in 25 patients) and Group- B (single layer interrupted sutures in 25 patients). After analysing the result of this study, it can be concluded that single layer repair for enteric perforation can be constructed in less time and with less complication rate compared with the conventional two layer repair technique, it also recovers the patient early and causing earlier bowel activity than two layer repair. Results: 50 patients were studied in the present study and results were in favour of single layer group as time taken for perforation repair and overall surgical time was less in this group. Moreover, single layer repair also helps early bowel activity and early recovery to the patient than double layer technique. Conclusions: Double layer closure of enteric perforation offers no definitive advantage over single layer repair in terms of faecal fistula formation, operative time, returns of bowel movements and other complications like wound abscess formation, wound dehiscence, respiratory complications etc. Less operative time and other factors in favour of single layer repair makes it the choice of procedure for most of the surgeons.